USING CHATGPT IN IT COURSES: PEDAGOGICAL APPROACHES AND IMPLEMENTATION EXPERIENCE - Bazhan, Stanislav (Collection of scientific papers «ΛΌГOΣ», 2026)
The integration of intelligent assistants, particularly ChatGPT, into the programming learning process opens new perspectives for the individualization of education and the provision of real-time student support. Recent studies increasingly emphasize that such systems can create an environment of continuous access to knowledge, facilitate the rapid correction of errors, and even foster self-directed learning skills. However, the effectiveness of this tool largely depends on how pedagogically well it is integrated into the curriculum.